The Main Telescope of The Ulugbek Observatory - Sayfullaeva Gulkhayo Ikhtiyor kizi; Mirzakandova Sohibjamol Kholmumin kizi (Zien Journals, 2022)
Our compatriots also made a great contribution to the study of celestial bodies. One of them is the grandson of Amir Temur Mirzo Ulugbek (1394-1449).
Keywords: research; Ulugbek Observatory; Jamshid al-Kashi; Kazi-zade Rumi